Guía para definir un sistema de control y valuación de inventarios analizando la viabilidad de incorporar Machine Learning (2020)
This work seeks to provide companies or whoever needs it, a guide that will allow them to learn theoretical concepts related to inventories and supply chain to define an inventory control and valuation system with the viability of incorporating Machine Learning, showing the theoretical advantages that It adds to the inventory control systems commonly used in Colombia.